Enhancing EFL students’ engagement in online synchronous classes: The role of the Mentimeter platform - Tarazi, Ayat; Ortega-Martín, José Luis (Frontiers in Psychology, 2023)
The present research aimed to evaluate teachers’ attitudes toward the use of the Mentimeter platform in synchronous education. This study also sought to delve into teachers’ perspectives on the role of the Mentimeter platform in improving students’ engagement in online synchronous classes. To that end, the study was carried out in Palestine in response to the ongoing shift to synchronous online teaching to raise teachers’ consciousness about the importance of using online tools to boost students’ engagement and make them feel connected in synchronous classes. A quantitative approach was used to collect data, and 44 Palestinian teachers from various educational institutions completed closed-ended questionnaires. The study’s outcomes demonstrated that teachers had positive attitudes toward employing the Mentimeter platform in synchronous education. The results also indicated that almost all educators perceived that the Mentimeter platform serves a vital role in increasing student engagement in online synchronous sessions. Teachers asserted that Mentimeter presentation styles decrease the probability of boredom among students, which in turn encourages them to actively participate in online synchronous classes. Enhancing students’ engagement in online synchronous classes was still a main challenge for educators. Therefore, to increase students’ involvement in synchronous learning environments, it is necessary to regularly train the teaching staff of schools, learning institutions, and colleges in the use of Mentimeter. Future studies in Palestine and other countries are also recommended to simultaneously concentrate on teachers’ and students’ viewpoints.